Actions speak louder : a step-by-step guide to becoming an inclusive workplace - Singh, Deanna (New York : Portfolio/Penguin, 2022)
"Actions Speak Louder is step-by-step guide for managers, DEI leaders, and individuals looking to creating diverse, equitable, and inclusive workplaces. DEI consultant Deanna Singh provides a blueprint for leaders and teams that includes step-by-step instructions for: gaining buy-in from stakeholders at all levels of the company for DEI initiatives; designing and implementing inclusive policies, from writing job advertisements to conducting performance reviews; and training DEI trainers"--
Includes bibliographical references and index.
Keywords: Diversity in the workplace; Teams in the workplace; Organizational change; Leadership